Synthesis and Antibacterial Activity of a Novel Class of Benzylidenrhodanine Based Furan Derivatives - Baharfar, Robabeh; Peiman, Sahar; Mohseni, Mojtaba (Letters in Organic Chemistry, 2014)
A simple synthesis of novel benzylidenrhodanine based Furan derivatives was described from 5-arylidene 3- carboxymethylrhodanine derivatives via multi-component reactions. The reactive 1:1 intermediate produced from the reaction of tert-butyl isocyanide and dialkyl acetylenedicarboxylates was trapped at room temperature by 5-arylidene 3- carboxymethylrhodanine derivatives to yield polyfunctionalized furan rings in fairly good yields. The products have been analyzed for antibacterial activity against Gram positive and Gram negative bacteria. The results indicated that the synthesized compounds are effective against bacterial growth retardation activity to some extent and their effectiveness is higher for Staphylococcusaureus.
Keywords: Dialkyl acetylenedicarboxylates